Metabolomics in herbal standardization and bioactivity assessment - Khatib, Alfi (2016)
Medicinal herbs have reached extensive acceptability as therapeutic agents for several diseases. However, the use of medicinal herbs constrained due to limitation on quality and safety assurance, as well as lack of scientific proof. Standardization is an important aspect for maintaining and assessing the quality and safety of medicinal herb. It includes raw plant authentification, microscopic & molecular examination, and identification of chemical composition. The challenge of natural chemists is to identify as much as possible the bioactive compounds and to study their mode of action to treat the diseases. This work is not easy due to the complexity of the compounds and limitation of time and budget. Lead finding with bioassay guided fractionation developing into high throughput screening could not increase the number of potential natural products in the pipeline of the pharmaceutical companies. Therefore, a new approach amends the inclusion of system biology in pharmacognosy research by using metabolomics as a tool. Metabolomics is a comprehensive analysis of the whole metabolites in a sample. Identification of both chemical and bio-markers can be performed by the instrumental analysis of both natural sources and animal biofluids and multivariate data analysis. All advanced instrumentation such as nuclear magnetic resonance spectroscopy, liquid chromatography-mass spectrometry, and gas chromatography-mass spectrometry are used in metabolomics.